Implementation of multisensor flood-emergency bags for protecting valuable documents in at-risk communities - Umi Salamah; Imam Azhari (Indonesian Journal of Community Services, 2026)
Felda Mata Air, Perlis, Malaysia, is one of the communities frequently affected by seasonal flooding, resulting in the loss of valuable documents and delayed emergency response. This community service program aimed to improve community preparedness through the implementation of a multisensor flood-emergency bag equipped with a water level sensor, audible alarm, LED indicator, GPS module, smartphone notification system, and waterproof document compartment. The program was conducted using a participatory approach consisting of community training, hands-on practice, field simulation, and mentoring. The effectiveness of the program was evaluated using pre-test and post-test assessments and analyzed using the normalized gain (N-Gain) method. The results showed that the average participant score increased from 5.49 to 7.78, representing a 41.54% improvement, with an N-Gain value of 0.51, indicating a moderate improvement in disaster preparedness knowledge. Participants also demonstrated the ability to operate the multisensor emergency bag independently during flood simulations. These findings indicate that integrating low-cost multisensor technology with community-based disaster education effectively enhances preparedness and contributes to protecting valuable documents during flood emergencies.